Association between diastolic blood pressure and cumulative work time Associação entre pressão diastólica e tempo de serviço - Ricardo Cordeiro; Euclydes Custódio de Lima Filho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
Diastolic blood pressure was viewed as a generic indicator of aging, and its association with cumulative work time was studied after controlling for age as a potential confounding factor. The study was conducted among production line workers at a Brazilian tannery in July 1993. The association between diastolic blood pressure and cumulative work time was verified by fitting a second-order linear regression model, where diastolic blood pressure was a function of worker's age and cumulative work time. By fitting the model, one can predict that, in the beginning of working life at the tannery, on average each 1-year period is associated with an increase of about 1.5 mmHg in diastolic blood pressure. The fit obtained highlights one component directly associated with work as part of the rate of pressure increase in the study group. This component is twice as high as that directly associated with age. A pressão arterial diastólica foi analisada enquanto indicador genérico de envelhecimento, e sua associação com o tempo de serviço foi estudada após o controle da idade como possível fator de confundimento. O estudo foi realizado entre operários de um curtume brasileiro em julho de 1993. Foi testada a associação entre pressão diastólica e tempo de serviço, ajustando um modelo de regressão linear de segunda ordem, em que a pressão diastólica era função da idade e do tempo de serviço do operário. Ao ajustar o modelo, pode-se prever que, no início do trabalho no curtume, em média, cada período de um ano está associado com um aumento de cerca de 1,5 mmHg na pressão diastólica. O ajuste obtido realça um componente diretamente associado ao trabalho como parte do coeficiente de aumento da pressão no grupo estudado. Esse componente é o dobro daquele diretamente associado com a idade.